2002
DOI: 10.1111/j.1432-2277.2002.tb00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset bacteremia in uncomplicated pediatric liver-transplant recipients after a febrile episode

Abstract: The aim of this study was to analyze the incidence and risk factors of bacteremia after a febrile episode in uncomplicated pediatric recipients more than 2 months after liver transplantation, which has not previously been studied. This crosssectional study was conducted over a 4-year period. Patients with known risk factors for sepsis at the time of admission were excluded from the study. Seventy-one patients were hospitalized on 128 occasions, with bacteremia occurring in the case of 11 admissions (8.6%). No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…These time periods were chosen for the purposes of the detailed risk analyses for infections, as they represent the peak periods for the development of these types of infections (5)(6)(7)(8)(9)(10). Infants are defined as <1 year of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These time periods were chosen for the purposes of the detailed risk analyses for infections, as they represent the peak periods for the development of these types of infections (5)(6)(7)(8)(9)(10). Infants are defined as <1 year of age.…”
Section: Discussionmentioning
confidence: 99%
“…All SPLIT centers have Institutional Review Board approval and individual informed consent is obtained from parents and/or guardians (5)(6)(7). Coded information is submitted to the SPLIT data-coordination center at the time of listing for liver transplant (LT).…”
Section: Patient Populationmentioning
confidence: 99%
“…11 Other investigators have similarly not found the complete blood count components predictive of bacteremia beyond 2 months posttransplant in pLTRs. 11,17 Across the 3 centers in our study, other inflammatory markers were infrequently obtained. Data in adults and children suggests that C-reactive protein and procalcitonin may be more sensitive biomarkers than the WBC, ABC or ANC to identify transplant patients with bacteremia.…”
Section: Discussionmentioning
confidence: 92%
“…The prevalence of bacteremia we noted was lower than previously reported, likely attributable to our restriction to those encounters in the outpatient rather than the inpatient setting. 6,17,18 However, bacteremia remained an important cause of infection in the first 2 years post-transplant.…”
Section: Discussionmentioning
confidence: 99%